Corporate governance, illiquidity, and valuation issues in privately-owned corporations - Chenchuramaiah T. Bathala; Oswald D. Bowlin; William P. Dukes (The Journal of Entrepreneurial Finance and Business Ventures, 2003)
Investors in private corporations face unique problems relating to corporate control, illiquidity and valuation of securities. In this research, we survey a large sample of US corporations. Our sample includes both private and public firms. Major findings of our research are as follows: Private firms use written shareholder agreements for safeguarding ownership interests and dividend payments. Family owned firms dominate the ownership structure of private firms. Insiders of private firms own a much larger proportion of common stock than insiders in public firms, and the CEOs of private firms often happen to be the largest stockholders.
Keywords: 650